Kurt Eisner : a modern life - Gurganus, Albert E. (Rochester, New York : Camden House, 2018)
The first comprehensive biography in English of the leader of the Bavarian Revolution and Republic of 1918/19, the first Jewish head of a European state and a man who embraced and embodied modernity.
Frontmatter -- CONTENTS -- ACKNOWLEDGMENTS -- INTRODUCTION -- 1. A Novel's Suffering Hero: A Youth in Berlin (1867-1889) -- 2. Aristocratize the Masses: From Berlin to Frankfurt to Marburg (1890-1893) -- 3. Refuge of All Idealists: Through Cohen to Kant toward Marx (1893-1896) -- 4. Dictatorial Megalomania: Lèse Majesté and Plötzensee Prison (1896-1898) -- 5. Making the Leap: Back to Berlin as a Social Democrat (1898-1900) -- 6. No Idle Dreamer: At the Helm of Vorwärts (1900-1902) -- 7. My Life's Purpose: Molding the Readership (1902-1903) -- 8. Never . . . a Less Fruitful Scholastic Debate: Intramural Strife -- Evolution vs. Revolution (1903-1905) -- 9. Revolutionizing Minds: The Scorched Middle Ground (1905) -- 10. The Complete Parity of My Experiences: From Exile to Nuremberg (1905-1907) -- 11. The Most Genuine and Fruitful Radicalism: Taking the Lead at the Fränkische Tagespost (1907-1908) -- 12. So Suspect a Heretic, as Surely I Am: New Bearings in North Bavaria (1908) -- 13. Dear Little Whore: Personal and Professional Turmoil (1909) -- 14. To Find a Lost Life: From Nuremberg to Munich (1909-1910) -- 15. Something of a Party Offiziosus in Bavaria: Political Editor at the Münchener Post (1910-1911) -- 16. At Peace with Myself: Resettling into Family Life (1912-1913) -- 17. The Powerlessness of Reason: The World War Erupts (1914) -- 18. Wretched Superfluity: Divided Loyalties (1915-1916) -- 19. War for War's Sake: Political Alienation and Realignment (1916-1917) -- 20. The Most Beautiful Days of My Life: Leading the Opposition (1917-1918) -- 21. Our Power to Act Now Grows: From Prisoner to Premier (1918) -- 22. The Terror of Truth: Forging the Republic, Combatting Reaction (1918) -- 23. The Fantasies of a Visionary: Martyr of the Revolution (1918-1919) -- 24. Now Dead, as It Stands: Outcomes and Legacy (1919-2017) -- Abbreviations -- Notes -- Sources and References -- Index
Online resource; title from PDF title page (EBSCO, viewed May 8, 2018).
Includes bibliographical references and index.
JSTOR
Keywords: Eisner, Kurt, -- 1867-1919.; Eisner, Kurt, -- 1867-1919; Socialists -- Germany -- Biography; Bavaria (Germany) -- History -- Revolution, 1918-1919.; Germany -- History -- Revolution, 1918.; Socialistes -- Allemagne -- Biographies; Bavière (Allemagne) -- Histoire -- 1918-1919 (Révolution); Allemagne -- Histoire -- 1918 (Révolution); HISTORY -- Europe -- Germany; Socialists; Germany; Germany -- Bavaria; 1918-1919; Bavarian republic; German Jews; Kurt Eisner; Munich revolution; political activism; pre-Nazi period; rise of fascism; Biography; Biographies; History; Biographies; Biographies